Effect of a repeated sprint ability test on the muscle contractile properties in elite futsal players - Sánchez-Sánchez, J.; Bishop, D.; Garcia-Unanue, J.; Ubago-Guisado, E.; Hernando, E.; López-Fernández, J.; Colino, E.; Gallardo, L. (Scientific Reports, 2018)
The aim of this study was to evaluate the effect of a repeated sprint ability (RSA) test on the contractile properties of the muscles in elite futsal players. A total of 20 elite players completed the RSA test (7×30 m), and the contractile response from the rectus femoris (RF) and biceps femoris (BF) of both legs were analysed pre and post through tensiomyography. There was a significant increment in 30-m times from the third sprint onwards (p<0.05). The percent decrement in sprint ability (RSADEC) with respect to the first sprint was significantly higher in the last sprint. The players did not show evidence of lateral asymmetry in any of the muscle groups analysed after the RSA test (p>0.05). Following the RSA test there was a significant reduction in the delay time (Td) in RF, a significant decrement in half-relaxation time (Tr) in the RF, and a significant reduction in sustain time (Ts) in the RF and BF of both legs. The maximum radial displacement of the muscle belly (Dm) increased (1.6 mm; effect size = 0.75; p<0.05) in the RF after the RSA test, indicating reduced muscle stiffness and the ability to generate strength rapidly. The decrement in performance during the RSA test was significantly correlated with changes in contraction time (Tc) in RF and BF, Td in BF, and Dm in RF (p<0.05). The RSA test generated alterations in the contractile properties of the RF and BF in elite players. However, futsal players did not present asymmetries in any muscular parameters. The baseline contractile muscle parameters could be an important factor related to performance of players during repeated high-intensity actions.